Contribute to the pivotal thinking skills in performing the transmission skill from Volleyball Fourth preparatory grade adolescents - Aziz, Heba; Al-Zuhairi, Najla (Journal of Physical Education, 2025)
The aim of this study was to identify the level of critical thinking skills among fourth-grade middle school students and to determine the performance level of the underhand volleyball pass, with the assumption that there is a positive relationship between critical thinking and skill performance. The study population included 281 students from Basra Preparatory School for Girls under the Second Baghdad Education Directorate for the 2024/2025 academic year, of whom 275 students were intentionally selected as the research sample (97.865% of the population). The experimental procedure involved applying a critical thinking scale and a technical performance test for the underhand pass on 25 students per day over 11 days, from February 9 to February 23, 2025, excluding Fridays and Saturdays. During this period, students had already been taught the underhand pass within the curriculum. Data were analyzed using SPSS, and results indicated that students possessed an acceptable level of critical thinking skills and an acceptable level of performance in the underhand pass. Moreover, higher levels of critical thinking were associated with improved skill performance, demonstrating a direct positive impact. The study recommends that physical education teachers incorporate critical thinking assessment and training into volleyball lessons to enhance both cognitive and practical skill development.